Dry matter and nitrogen accumulation of sweet corn (Zea mays var. saccharatta L.) under salt stress - Sukma, Kelik P W; Awidiyantini, Ruly (Agrovigor, 2024)
Sweet corn is popular among consumers due to its sweet taste, with ‘Bonanza’ being a variety widely cultivated by farmers in Madura. This research aimed to determine the dry matter and nitrogen accumulation in 'Bonanza' sweet corn under salt stress conditions. 'Bonanza' corn seedlings were grown in polybags containing a 1:1 mixture of soil and sand in a completely randomized design, with salt treatments of 0, 100, and 200 mM NaCl applied every two weeks. Each treatment was replicated eight times. Observed parameters included total plant weight, weight distribution of plant parts (roots, stems, leaves, tassels, ears, and seeds), percentage weight of plant parts, shoot/root ratio, and total nitrogen content in roots, stems, leaves, and seeds. Data were analyzed using one-way ANOVA followed by LSD post-hoc testing in SPSS 24. Results indicated that salt stress generally reduced total plant weight and the weights of individual plant parts. However, salt stress increased dry matter accumulation in leaves and stems, 2.5 and 8% respectively at a 100 mM increase in salt content, while decreasing it 11% in ear and 7.5% in seeds. Additionally, salt stress increased total nitrogen content in root, stems and leaves (average 2.6%) under but decreased in seeds (0.19%).